Desingn of mercury (II) adsorption sites on high disperse silica surface - Belyakova, L. A.; Lyashenko, D. Yu.; Shvets, O. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
Adsorption has been sutied of Hg (II) ions with hydroxylated silica, aminopropylsilica, and silicas chemically modified with b-cyclodextrin derivatives. The kinetics of Hg (II) adsorption as tested within the Lagergren model for the pseudo-first and pseudo-second order processes, the adsorption isotherms being fitted to the Freundlich and Langmuir equations. The β-cyclodextrin-containing adsorbents were found to have high affinities to Hg (II) due to “ β-cyclodextrin – nitrate-ion” inclusion complexes and super molecules formed on their surfaces. The chemical composition of super molecules correlates with stability of mercury (II) surface complexes.